2019
DOI: 10.3389/fenrg.2019.00036
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Level Aggregator Platform for DSO Support—Integration of Storage, Demand Response, and Renewables

Abstract: Modern era is full of renewable energy resources, particularly wind and solar that are installed at both Low and Medium voltage nodes of the distribution system. With the diffusion of new resources in the distribution grid, a new challenge for the system operators is to cope up with the introduced changes in the distribution network. These changes can be on voltage levels, magnitudes and direction of current, and changes in power factor. The reduced visibility of these additives to operators require provision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…while a huge capacity of wind generations will be integrated in the grid. The authors in [26] present a platform for distribution level aggregators to serve as sub demand side operator in terms of the electrical energy storage system, customers DR, and the renewable resources (PV and wind). Four types of consumers such as residential, commercial, aggregated, and residual have been considered to provide a real power reserve via DR programs.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…while a huge capacity of wind generations will be integrated in the grid. The authors in [26] present a platform for distribution level aggregators to serve as sub demand side operator in terms of the electrical energy storage system, customers DR, and the renewable resources (PV and wind). Four types of consumers such as residential, commercial, aggregated, and residual have been considered to provide a real power reserve via DR programs.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…With the help of DER aggregators, the scheduling pressure of power system operators can be shifted downstream [5]. However, aggregators themselves have to find an effective way to organize profit-seeking DER individuals and their volatile outputs.…”
Section: A Motivationsmentioning
confidence: 99%
“…Regardless of the aggregator chosen by DER i, its values of Cit in (4)-( 5) are utilized in a tamper-evident manner by a blockchain. The logarithmic and linear forms in (5) can control the rate of growth or decline in subjective credits, respectively, while the cumulative effect of historical credit decreases over time.…”
Section: B Po2c Consensusmentioning
confidence: 99%
“…In some studies, DSOs were proposed to deploy the flexibility potential of demand-side resources for operating their local distribution networks. For instance, in [23], it was suggested that the DSO assigns its responsibilities to some aggregator. The aggregators utilize EVs, renewable energy resources, and demand response to operate their own local networks.…”
Section: ) Local Flexibility Provisionmentioning
confidence: 99%